Social comparison and continuance intention of smart fitness wearables: an extended expectation confirmation theory perspective. Issue 13 (3rd October 2021) - Gupta, Anil; Dhiman, Neeraj; Yousaf, Anish; Arora, Neelika
ABSTRACT: Technological innovations, especially smart fitness wearables, are playing a critical role in the future of fitness and overall well-being. Extant research has examined the adoption of smart fitness wearables, with limited attention paid to continuance intention. The current study attempts to investigate users' continuance intentions of using smart fitness wearables by combining expectation confirmation theory and social comparison theory. In particular, this paper extends the expectation confirmation model by adding perceived health outcomes and social comparison tendency to understand the continuance intention of smart fitness variables. The model explains 72.8% of continuance intention, and the findings reveal that perceived health outcome and users' satisfaction predict continuance intention leading to intention to recommend. Furthermore, the findings confirm the positive impact of social comparison tendency on perceived health outcome and users' satisfaction. Users' satisfaction is influenced by perceived usefulness, confirmation, perceived health outcome and social comparison tendency. Our study confirms that mere post-adoption perceived usefulness does not guarantee continuance intention, unless the perceived health outcomes are achieved.